Antiferrodistortive phase transition in Pb(Ti0.48Zr0.52)O3: Space group of the lowest temperature monoclinic phase - Hatch D.M.; Stokes H.T.; Ranjan R.; Ragini; Mishra S.K.; Pandey D.; Kennedy B.J. (My University, 2025)
Ranjan et al. [Phys. Rev. B 65, 060102(R) (2002)] have recently presented results of a powder neutron-diffraction study of the high-temperature monoclinic (FMHT) to low-temperature monoclinic (FMLT) phase transition in Pb(Ti1-xZrx)O3 discovered by Ragini et al. [Phys. Rev. B 64, 054101 (2001)]: They attribute the presence of superlattice reflections in the diffraction data to tilting of oxygen octahedra and propose a monoclinic space group Pc for the FMLT phase. It is shown that for the model proposed by Ranjan et al., the correct space group of the FMLT phase should be Cc. This has also been corroborated by a group-theoretical approach to the problem. A different set of refined structural parameters for the Cc space group obtained from the Rietveld analysis of the powder neutron-diffraction data of Ranjan et al. is also presented.